PROTECTING NATIONAL IDENTITY BASED ON THE VALUE OF NATION LOCAL WISDOM - Habibi Habibi (International Journal of Malay-Nusantara Studies, 2018)
The national scale of national unity is a noble idea that will ultimately lead to peace. Contemplating the recent social reality, it seems that the willingness to build peace needs more serious consistency. This is constituted on social phenomena that are born massively and at once tends to undermine national unity. The emergence of horizontal conflicts that bring out SARA issue managed to threaten peace. Interestingly, this phenomenon often appears ahead of the political contestation. Therefore, to guarantee a healthy democratic system and support national integration. Therefore, through the values of local wisdom is expected to reduce the problems above. This paper aims to explain the cause of the fertile of negative issues and to examine more deeply related to the values of local wisdom. The method of writing used is literature analysis. The results of the analysis found that behind the proliferation of the SARA issue that triggers social conflict is a phenomenon built by political entrepreneurs to support personal interests. This is marked by the time when the issue arose when the political year was approaching. Thus, social conflict is not a natural product of communal society, but a product of deliberate political strategy. It is concluded that reconstructing the value of local wisdom becomes the most concrete solution in overcoming the problems related to national unity and coalescence.